2021
DOI: 10.1186/s12645-021-00106-7
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic action of curcumin and cisplatin on spinel ferrite/hierarchical MCM-41 nanocomposite against MCF-7, HeLa and HCT 116 cancer cell line

Abstract: Background Platinum-based drugs are widely used in cancer therapy, but are known for toxic side effects and resistance. Combinational drug delivery represents an effective chemotherapeutic strategy, but often leads to an increased toxicity. Aim of this study is to test the co-delivery of cisplatin with natural antioxidants on hierarchial porous large surface area hexagonal nanocarriers for synergistic action. Results A series of structured mesoporo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Furthermore, at a lower concentration of 5 mg/mL, the cellular viability percentage of healthy HEK293T cells is close to 90%. Meanwhile, in inquiry on CuFe 2 O 4 /mesosilicalite synthesized on HFF (human foreskin fibroblasts) cell lines 46 , where nanocomposite reached only 87% viability at a concentration of only 0.1 mg/mL. In addition, it has been reported that the antibacterial properties of CuFe 2 O 4 nanoparticles have been decreased after being covered or functionalized 47 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, at a lower concentration of 5 mg/mL, the cellular viability percentage of healthy HEK293T cells is close to 90%. Meanwhile, in inquiry on CuFe 2 O 4 /mesosilicalite synthesized on HFF (human foreskin fibroblasts) cell lines 46 , where nanocomposite reached only 87% viability at a concentration of only 0.1 mg/mL. In addition, it has been reported that the antibacterial properties of CuFe 2 O 4 nanoparticles have been decreased after being covered or functionalized 47 .…”
Section: Resultsmentioning
confidence: 99%
“…As part of the cisplatin adsorption study, the following nanocarriers (Ti 3 C 2 -Fe 3 O 4 @SiO 2 -FA and Ti 3 C 2 @ FA) (1 mL) loaded formulations were mixed separately with various masses of Cisplatin (0.5, 1, 1.5, 2, 3 mg) of Cisplatin in 20 mL of Phosphate-buffered saline solution (PBS) under an ice-cooled dark environment ( Jermy et al, 2019 ; 2021 ). After overnight stirring and sonication at room temperature, the solution mixture was centrifuged at 8,000 rpm for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Phase separation and ionic gelation methods were mainly implemented to prepare nano-chitosan biocomposites (Ramezani Farani et al 2022;Vaezifar et al 2013). Its functionalization with folic acid is considered a good substance for the delivery of molecules due to its high solubility in water, excellent biocompatibility, and biodegradability (Jermy et al 2021(Jermy et al , 2019. Upon further investigation, it was found that nano-chitosan functionalized by FA behaved highly dependently on the pH value of the solution (Farahnak Roudsari et al 2021).…”
Section: Introductionmentioning
confidence: 99%